Sosialisasi Kato Nan Ampek Sebagai Penguatan Karakter Siswa SDN 09 Padang Sibusuk - Apriyano, Berto; ., Nadiva; Fasha, Antika Rahmadia; Yunita, Revi; Roza, Mila; Putri, Anisa; Leonardi, M. Aji; Sari, Luthfita; Rifarzy, Muhammad (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Inclusive education requires learning approaches that are adaptive to students’ diversity, including social, cultural, and linguistic aspects. One relevant approach is the integration of local wisdom into contextual learning processes. This study aims to describe the implementation and analyze the role of Kato Nan Ampek socialization as a culture-based approach in supporting inclusive learning and strengthening students’ character. The study was conducted through a Community Service Program (KKN) using a participatory educational approach involving third-grade students of SD Negeri 09 Nagari Padang Sibusuk. The implementation methods included preliminary observation, material delivery, interactive discussions, and simulation or role-playing activities. Data were collected through observation, question-and-answer sessions, and student reflections. The results showed that initially, most students had limited understanding of the Kato Nan Ampek concept. However, after the socialization activities, there was a significant improvement in students’ understanding and their ability to apply polite communication according to social contexts. Simulation methods proved effective in facilitating the internalization of values such as sensitivity (raso), reflection (pareso), politeness, and compassion. Nevertheless, sustaining these values in daily life remains a challenge. Therefore, more contextual and sustainable pedagogical strategies are needed to ensure the effective internalization of Kato Nan Ampek values in students’ everyday behavior.